The acquisition of intercultural competence in language courses - Samarina, V. V.; Shamrai, O. V.; Самаріна, В. В.; Шамрай, О. В.; Самарина, В. В.; Шамрай, Е. В. (Харківський національний автомобільно-дорожній університет, 2019)
This thesis deals with teaching foreign language and the importance to develop intercultural skills and know-how which include the ability to bring one’s own cultural origins and the for-eign culture into relation with each other, together with the ability to understand and empathize with the values and conditions of others. The language learner needs to develop other skills than sociocultural knowledge and have to improve interpersonal relations and develop intercultural awareness.
Формування міжкультурної компетенції на заняттях з іноземної мови
Формирование межкультурной компетенции на занятиях по иностранному языку
Keywords: language teaching; foreign language; intercultural competence; intercultural skills; навчання мовам; іноземна мова; міжкультурна компетентність; міжкультурні навички; обучение языкам; иностранный язык; межкультурная компетентность; межкультурные навыки; 81’243:316.722=821.111; 10.30977/BUL.2219-5548.2019.87.0.138